DIFFERENT APPROACHES OF TRANSLATING OF PHRASEOLOGICAL UNITS (KONFERENSIYA, 2025)
This article examines the translation of phraseological units between closely relatedand distant languages, highlighting the strategies necessary to preserve both meaningand stylistic value. The study discusses common translation methods—equivalent,analogical, and calque (literal reproduction)—and emphasizes instances where noneof these strategies are sufficient, requiring the use of descriptive translation